A deep insight into carbon conversion during Zhundong coal molten salt gasification. (15th May 2018) - Xu, Mian; Hu, Hongyun; Yang, Yuhan; Huang, Yongda; Xie, Kang; Liu, Huan; Li, Xian; Yao, Hong; Naruse, Ichiro
Highlights: A general pathway of carbon conversion in coal molten gasification was concluded. Feeding mode played a significant role in the molten gasification of coal. The condensation/graphitization of the char was stimulated in the molten eutectics. More carbonyl groups were formed in molten salt with carbonates as oxygen supplier. Decomposition of carbonyl inside char was suppressed by COx transfer resistance. Abstract: Molten salt gasification is a promising way for collaborative use of solar energy and Zhundong coal, with in situ capture of Cl/S-pollutants as well as alkali metals. The present study provides a deep insight into carbon conversion during molten salt gasification of a typical Zhundong coal in ternary carbonate eutectics (Li2 CO3 -Na2 CO3 -K2 CO3 ). The results demonstrated that the molten salt gasification of Zhundong coal underwent a rapid devolatilization of raw coal and then the gasification of char. The interactions between CO2 and volatiles promoted the cracking of macromolecular compounds, increasing the carbon conversion efficiency during the devolatilization process. The gasification of char was mainly determined by the direct reaction with molten salt, which was slightly affected by the CO2 concentration in the carrier gas. The results of char characterization evidenced that the condensation/graphitization of char was stimulated in the molten eutectics. Meanwhile, a large amount of O-containing groups, especially carbonyl groups, were formed in the molten salt treated char with carbonates as oxygen supplier. Under the influence of molten salts, some carbonyl groups would be formed inside the char. However, the decomposition of those carbonyl groups was suppressed by the mass transfer resistance of the released CO and/or CO2 . Applying proper feeding mode, such as feeding coal in pulverized form, could enhance the contact of coal, molten salt and CO2, which remarkably promoted the interactions between molten salts and char containing functional groups.